In vitro bioassay of secondary metabolites of soybean (Glycine max) plant roots and their effect on growth of bacteria, hormones and plants - RAGHAV, RANJEET SINGH; KHICHI, DHARMENDRA SINGH; SINGH, Y V (The Indian Journal of Agricultural Sciences, 2019)
Legume plants produce a high diversity of natural secondary metabolites with a prominent function that is important for the communication of the plants with other organisms and are significant for growth and development processes. In the present experiment, 50 roots of soybean [Glycine max (L.) Merr], were selected from the fields during 2016 to study the effect of root metabolites on bacterial growth and their growth hormone production potential. Bioassay was performed on the germination of chickea (Cicer arietinum L.) plant. The results indicated that the secondary metabolites of legume root enhance bacterial growth. It was found that the bacterial (Pseudomonas) growth was concentration dependent and was highest at the highest concentration of root extract, reflected by its maximum cell count. The highest cfu count (254 Ã— 105 cfu/ml) of Pseudomonas was obtained in culture medium containing 100% root extract after 48 hr incubation. The amounts of IAA and GA produced at this concentration were 387.9 Î¼g/25ml and 103.87 Î¼g/25 ml, respectively. The production of IAA and GA was maximum in root extract containing media. It was observed that root extract was most effective in inducing seed germination and multiple root production. It was concluded that root extract played a vital role in the in vitro plant growth hormone (IAA and GA) production and enhancement of growth of chickpea plant.